PENGARUH PEMBERIAN TRICHOKOMPOS KULIT BUAH KOPI DENGAN KADAR AIR TANAH YANG BERBEDA TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao) DI POLYBAG - . Rinaldi; . Mapegau; Maria Francisca (Bioplantae, 2012)
This Research was obtained to determine the effect of different doses of Trichocompost from cacao fruits leather on the growth of cacao at the diffeerent soil water level. It was conducted at Agriculture Faculty Research Fram, Mendalo Darat. This research was arranged at Randomized Complete Design with 16 combination of Trichocompost adn soil water level. The Frist Factor : doses were 0 g/polibag, 150 g/polybag, 300 g/polibag ang 450 g/polybag, and the second Factor : Soil water level 25 % field capacty, 50% field capacity, 75 % field caporacity and 100 % field capacy. The result showed that, trichocompost can reduced the less of soil water content at doses 300 g/polybag cacao fruits leather whit 50 percent of fileed capacityKata kunci : Cacao, Fruits leather, Trichocompost.